Salivary pH changes under the effect of stainless steel versus elastomeric ligatures in fixed orthodontic patients: a single-center, randomized controlled clinical trial - Hend Abulkarem Abdullah Al-Haifi; Ramy Abdulrahman Ali Ishaq; Maged Sultan Abdullah Al-Hammadi (BMC, 2021)
Abstract Background Fluctuations in pH of saliva during a prolonged treatment course influences the enamel demineralization progress, which is one of the complications of fixed orthodontic treatment. This randomized clinical trial aimed to evaluate and compare the short-term effects of stainless steel (SS) versus elastomeric (EM) ligatures on salivary pH in patients scheduled for fixed orthodontic treatment. Methods Seventy participants were enrolled in the study (54 female, 16 male) aged 19-36 years who met specific inclusion criteria. They were randomly selected and allocated into two equal groups through computer-generated randomization. All patients received fixed orthodontic treatment using conventional orthodontic brackets. Two commonly used archwire ligature methods were used: SS and EMs. An unstimulated (resting) salivary sample was collected before tying of the ligatures at T0 (baseline), 2 weeks, 6 (weeks), and 12 (weeks). Salivary pH was measured using a digital pH meter. The level of significance was set at p value < 0.05. Results The salivary pH level was stable between T0 and T1 (6.72 ± 0.14), then significantly and progressively increased from T1 to T2 (6.78 ± 0.13) and from T2 to T3 (6.81 ± 0.14) with (p < 0.05) in the SS group. In the EM group, the salivary pH level was significantly decreased in all follow-up periods; T0 (6.77 ± 0.16), T1 (6.72 ± 0.14), T2 (6.67 ± 0.13) and T3 (6.64 ± 0.13). Conclusion The EM ligatures showed a significant decrease in salivary pH to an unfavorable level, which increased the risk of enamel demineralization. Therefore, EMs as ligature material is preferably should not be recommended in patients with high caries index or inadequate oral hygiene. Trial registration ANZCTR.org. (ACTRN12618001647224) http://www.anzctr.org.au/ACTRN12618001647224.aspx . Registration Date: 5/10/2018, "Retrospectively registered".